Hydrodynamic force of a circular cylinder close to the water surface. (30th July 2018) - Chu, Chia-Ren; Lin, Yu-An; Wu, Tso-Ren; Wang, Chung-Yue
Highlight: The LES model and VOF method is used to study free surface flows over a circular cylinder. The effects of the gap ratio, depth ratio and Froude number on the force coefficients were analyzed. The pressure on the cylinder is affected by the water surface when the gap ratio less than 1.50. When the water depth drop behind the cylinder, the drag coefficient increases. Abstract: The hydrodynamic loadings on underwater pipelines are essential parameters for pipeline design. This study integrates a Large Eddy Simulation (LES) model and the Volume of Fluid (VOF) method to examine the interaction between free surface flows and a horizontally-mounted circular cylinder. The simulated water depths and surface pressures on the cylinder were verified by the results of laboratory experiments. The numerical model was then utilized to inspect the effects of the Froude number, gap ratio and depth ratio on the flow field and the force coefficients of the submerged circular cylinder. The simulation results revealed that the effects of the water surface occur when the gap ratio h / D  ≤ 1.50. The Strouhal number first increased, and then decreased as the cylinder came close to the water surface. The vortex shedding was completely suppressed when the water depth drop behind the cylinder and the downstream was a super-critical flow. In addition, when the downstream water depth changed significantly, the drag coefficient CD of the cylinder was larger than that of the cylinder in an unbounded flow. The lift coefficient increased from 0 to 0.80 as the gap ratio h / D decreased, due to the asymmetric pressure distribution.